Antistatic and antibacterial mixed fiber and preparation method thereof
By performing stepwise grafting modification and finishing processes on polycaprolactam and polyethylene terephthalate fibers, the durability issues of antistatic and antibacterial properties of textile fabrics were solved, achieving highly efficient antistatic and antibacterial effects and improving the washability and comfort of the fabrics.
Patent Information
- Application Number
- CN202511199437.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-12-02
AI Technical Summary
Existing textile fabrics cannot simultaneously possess both long-lasting antistatic and antibacterial properties, and the existing technologies and processes are complex and have poor functional durability, affecting the breathability and comfort of the fabrics.
By performing stepwise graft modification of polycaprolactam and polyethylene terephthalate fibers, combined with post-treatment processes, antistatic and antibacterial functions are constructed. High-concentration quaternary ammonium salt monomers and crosslinking agents are used to form chemical bonds, and silver-doped nano-titanium sol and waterborne polyurethane are combined for multi-component finishing to ensure the durability and synergistic effect of the functions.
The antistatic properties of the fiber material were maintained at ≥90% and the antibacterial properties at ≥90% after 50 washes, significantly improving the functionality, durability, and comfort of the fabric.
Smart Images

Figure BDA0005566072790000031 
Figure BDA0005566072790000061 
Figure BDA0005566072790000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile fabric technology, specifically to an antistatic and antibacterial blended fiber and its preparation method. Background Technology
[0002] In modern society, the functional requirements of fabrics have evolved from basic warmth and coverage to more refined aspects, with antistatic, antibacterial, ventilation, and quick-drying properties becoming the development direction for high-end functional fabrics.
[0003] The demand for antistatic and antibacterial functions stems from practical pain points in multiple fields and is a typical example of how scenario-based applications drive the upgrading of material technology.
[0004] In the healthcare field, the risk of microbial growth and cross-infection in hospital environments is extremely high. While traditional fabrics can provide basic protection, they are insufficient to inhibit the attachment and reproduction of bacteria, fungi, and other microorganisms, easily becoming a medium for the spread of hospital-acquired infections. Furthermore, the protective suits and surgical gowns worn by medical staff are prone to generating static electricity during friction, which may not only interfere with the normal operation of precision medical equipment but also attract dust particles from the air, affecting the cleanliness of the environment.
[0005] The electronics and information industry has even more stringent requirements for anti-static properties. In the production and assembly environments of semiconductor chips and precision electronic components, electrostatic discharge (ESD) can cause component breakdown and performance failure, resulting in huge economic losses. If the work clothes worn by relevant workers do not have anti-static properties, the static voltage generated by friction can reach thousands of volts, far exceeding the tolerance threshold of electronic components. In addition, the high humidity environment of electronic cleanrooms can easily cause microorganisms to grow on the fabrics, affecting the cleanliness of the production environment.
[0006] In everyday wear, functional needs are becoming increasingly prominent. Sportswear, underwear, and other close-fitting fabrics are prone to developing odors due to microbial growth after the body sweats, affecting the wearing experience; static electricity generated by friction of synthetic fiber fabrics not only causes clothing to attract dust and cling to the body, but may also produce an electric shock sensation when in contact with metal objects, causing discomfort to the user.
[0007] To meet the needs of antistatic or antibacterial properties, existing technologies have developed a variety of functional fabrics, but single-function or simple composite products still have obvious limitations.
[0008] The technical approaches to antistatic fabrics mainly fall into two categories: The first involves coating the fabric surface with an antistatic finishing agent, introducing hydrophilic groups to increase the fabric's conductivity and allow the charge to dissipate quickly. This method is relatively low-cost, but the finishing agent is easily removed during washing and friction, resulting in poor functional durability and potentially affecting the fabric's breathability and feel. The second approach involves blending or interweaving conductive fibers (such as carbon fiber, metal wire, and conductive polyester) with ordinary fibers to achieve an antistatic effect by constructing a conductive network. This type of fabric has better functional durability, but the addition of conductive fibers may reduce the fabric's softness and comfort, and metal fibers are prone to corrosion, affecting the fabric's lifespan.
[0009] The technical solutions for antibacterial fabrics are also diverse: metal ion antibacterial (such as silver ions and zinc ions) is the most widely used method. This involves loading metal ions onto the fabric surface or inside the fibers, utilizing the bactericidal effect of the metal ions to achieve antibacterial function. Its antibacterial effect is long-lasting, but high concentrations of metal ions may irritate human skin, and the high valence state of silver ions also increases the cost of the fabric. Natural antibacterial agents (such as chitosan and plant essential oils) have attracted attention due to their high safety, but their antibacterial effect is relatively weak and easily degraded by environmental temperature and humidity. Organic antibacterial agents (such as quaternary ammonium salts and guanidine compounds) have high antibacterial efficiency, but poor chemical stability; long-term use may lead to drug resistance in microorganisms.
[0010] Currently, most fabrics that possess both antistatic and antibacterial properties employ a layered process of "antistatic and antibacterial dual finishing agents," meaning the base fabric is first treated with antistatic agents, followed by an antibacterial coating. This simple composite method is not only complex but may also reduce the functional effect due to the interaction between the two finishing agents, and can easily lead to problems such as a stiffer fabric feel and reduced breathability. Summary of the Invention
[0011] The purpose of this invention is to provide an antistatic and antibacterial blended fiber and its preparation method to solve the problems mentioned in the background art.
[0012] A method for preparing an antistatic and antibacterial blended fiber includes the following steps:
[0013] S1 fiber pretreatment: polyethylene terephthalate fibers and polycaprolactam fibers are washed and then dried; then activated to obtain activated polyethylene terephthalate and polycaprolactam;
[0014] S2 polycaprolactam graft modification: Quaternized dimethylaminoethyl methacrylate, N,N'-methylenebisacrylamide and emulsifier are added to deionized water, stirred to dissolve and the pH is adjusted to 6.0 to obtain electrostatic modified solvent;
[0015] The activated polycaprolactam was immersed in an electrostatically modified solvent and deoxygenated, and then an initiator was added and the mixture was heated in a water bath for reaction.
[0016] After the reaction was complete, the reactants were washed and then dried to obtain modified polycaprolactam.
[0017] S3 polyethylene terephthalate graft modification: 2-methacryloyloxyethyltrimethylammonium chloride and N,N'-methylenebisacrylamide are added to deionized water; the mixture is stirred to dissolve and the pH is adjusted to 6.0 to obtain a sterile modified solvent;
[0018] The activated polyethylene terephthalate was immersed in a sterile modified solvent and deoxygenated, and then an initiator was added and the mixture was heated in a water bath for reaction.
[0019] After the reaction was complete, the reactants were washed and then dried to obtain modified polyethylene terephthalate.
[0020] S4 blending treatment: Modified polycaprolactam and modified polyethylene terephthalate are placed separately into a screw press and spun together at a mass ratio of 3-4:6-7 to obtain the base fabric;
[0021] S5 finishing: The base fabric is immersed in the finishing agent and then treated by padding-baking method to obtain antistatic and antibacterial blended fiber.
[0022] Preferably, in step S2, the quaternized dimethylaminoethyl methacrylate is generated by a nucleophilic substitution reaction between dimethylaminoethyl methacrylate and a haloalkane.
[0023] The electrostatically modified solvent contains the following components by concentration:
[0024] Quaternized dimethylaminoethyl methacrylate ≥150g / L
[0025] N,N'-methylenebisacrylamide ≥4.5 g / L
[0026] Emulsifier ≥1g / L.
[0027] When the activated polycaprolactam is immersed in the electrostatically modified solvent, the bath ratio is 1:≥50; the amount of initiator added is...
[0028] ≥1.5mmol / L; heating water bath reaction temperature ≥55℃, time ≥3h.
[0029] Preferably, in step S3, the antibacterial modified solvent contains the following components by concentration:
[0030] 2-Methacryloxyethyltrimethylammonium chloride ≥120g / L
[0031] N,N'-methylenebisacrylamide ≥2.4 g / L.
[0032] In step S3, when the activated polyethylene terephthalate is immersed in the sterile modified solvent, the bath ratio is 1:
[0033] ≥40; the amount of initiator added is ≥1.5mmol / L; the temperature of the water bath reaction is ≥65℃, and the time is ≥2.5h.
[0034] Preferably, in step S5, the finishing agent contains the following components by concentration:
[0035]
[0036] The silver-doped nano-titanium sol contains at least 1.5 wt% silver; the aqueous polyurethane has a solid content of ≥30%.
[0037] The dip-and-bake method involves at least two dips and two rolls, with a roll-off rate ≥75%; the baking temperature is ≥150℃ and the baking time is ≥2min.
[0038] This invention constructs a complete process system from fiber pretreatment to finishing. The pretreatment removes impurities and enhances fiber surface activity through cleaning, drying, and activation, laying a foundation for efficient reaction in subsequent modification. It innovatively targets and modifies polycaprolactam (focusing on antistatic properties) and polyethylene terephthalate (focusing on antibacterial properties), fully leveraging the advantages of both substrates and avoiding functional conflicts. The padding-baking finishing process further consolidates the modification effect through a combination of physical adsorption and chemical fixation, effectively solving the potential functional loss problem associated with single grafting, forming a complete performance guarantee chain of "pretreatment-modification-blending-reinforcement".
[0039] This invention clarifies that quaternized dimethylaminoethyl methacrylate is generated via a nucleophilic substitution reaction between dimethylaminoethyl methacrylate and a haloalkane. The nucleophilic substitution reaction mechanism is clear, with few byproducts; the resulting quaternary ammonium salt exhibits high chemical stability, and its antistatic effect is not easily affected by environmental humidity and temperature, demonstrating significantly better durability than physically adsorbed antistatic agents.
[0040] This invention defines the minimum concentrations of quaternized monomers, crosslinking agents, and emulsifiers in the electrostatic modification solvent. High concentrations of quaternized monomers provide sufficient antistatic functional groups for polycaprolactam fibers, ensuring a significant improvement in fiber surface conductivity; sufficient crosslinking agents firmly anchor the quaternary ammonium groups by forming a three-dimensional network structure, greatly reducing functional loss due to washing or friction; and the emulsifier ensures uniform dispersion of the monomers in water, avoiding localized aggregation and guaranteeing consistent antistatic properties of the fibers.
[0041] This invention also limits the lower concentration limits of 2-methacryloyloxyethyltrimethylammonium chloride and crosslinking agent in the antibacterial modified solvent, which has the advantage of enhancing the effectiveness and durability of antibacterial function. High-concentration cationic antibacterial monomers ensure sufficient density of antibacterial groups on the fiber surface after grafting, significantly enhancing the adsorption and killing ability against pathogenic bacteria such as Escherichia coli and Staphylococcus aureus. The appropriate amount of crosslinking agent fixes the antibacterial groups on the surface of polyethylene terephthalate through covalent bonds, effectively solving the problem of easy detachment of traditional physically coated antibacterial agents. Considering the high chemical stability and difficulty in modification of polyester, the high-concentration monomer design significantly improves the grafting success rate, ensuring precise realization of antibacterial function.
[0042] This invention also includes post-treatment, a multi-component design of the finishing agent (including polythiophene, silver-doped nano-titanium sol, waterborne polyurethane, etc.), and key indicator limits (silver ≥ 1.5 wt%, waterborne polyurethane solid content ≥ 30%), aiming for synergistic functional enhancement and controllable performance. Polythiophene enhances antistatic properties, silver-doped nano-titanium sol strengthens broad-spectrum antibacterial properties (covering bacteria and fungi), and waterborne polyurethane improves film adhesion and abrasion resistance. The complementary nature of the multiple components achieves a comprehensive improvement in antistatic, antibacterial, and durability. Polyvinylpyrrolidone improves nanoparticle dispersibility, and citric acid and sodium acetate stabilize the reaction environment, enhancing the stability of the finishing agent during storage and use. Clearly defined lower limits for silver content and polyurethane solid content ensure that antibacterial efficiency and film strength meet standards, avoiding functional failure due to insufficient components.
[0043] This invention specifies a two-dip, two-nip process, a liquid fill rate (≥75%), and baking conditions (≥150℃ / ≥2min). Its advantages lie in ensuring sufficient adhesion and firm fixation of the finishing agent. The two-dip, two-nip process, through multiple dips and squeezes, ensures uniform penetration of the finishing agent into the fiber's interior and surface. The high liquid fill rate (≥75%) guarantees sufficient dosage, avoiding localized functional deficiencies. High-temperature baking above 150℃ promotes cross-linking between the active groups of the finishing agent and the fiber surface groups, while simultaneously evaporating moisture and solidifying the film, significantly improving wash resistance (high functional retention rate after multiple washes). Clearly defined lower limits for process parameters reduce performance fluctuations caused by operational deviations during production, providing stable and controllable process conditions for continuous industrial production.
[0044] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention achieves long-lasting antibacterial effects by stepwise grafting modified PA6 (polycaprolactam) fibers loaded with quaternary ammonium salts, and grafting cationic monomers onto PET (polyethylene terephthalate) fibers to construct antistatic pathways. The two are blended in a 6-7:3-4 ratio, balancing performance and mechanical strength. The finishing process employs a polythiophene conductive layer and silver-doped nano-titanium sol, imparting dual antibacterial properties and highly efficient antistatic properties to the surface. In terms of process, this invention significantly improves environmental friendliness and production efficiency through an aqueous reaction system and a pad-drying method, achieving a functional retention rate of ≥90% after 50 washes. Detailed Implementation
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] Example 1: A method for preparing mixed fibers, comprising the following steps:
[0047] S1 fiber pretreatment: Polyethylene terephthalate fiber and polycaprolactam fiber were soaked in 5 g / L NaOH solution (60℃) for 30 min to remove surface oil and impurities, rinsed with deionized water until neutral, and vacuum dried at 80℃ for 4 h.
[0048] Then, under an oxygen atmosphere, the surface-active groups were increased by plasma treatment at 50W for 5 minutes to obtain activated polyethylene terephthalate and polycaprolactam.
[0049] S2 polycaprolactam graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare an electrostatic modification solvent;
[0050] 150 g / L of quaternized dimethylaminoethyl methacrylate
[0051] N,N'-Methylenebisacrylamide 4.5 g / L
[0052] Sodium dodecyl sulfate 1 g / L.
[0053] The activated polycaprolactam was immersed in an electrostatically modified solvent with a bath ratio of 1:50; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0054] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 55°C for 3 hours.
[0055] After the reaction was completed, the product was washed three times with deionized water at 80°C to remove ungrafted monomers and homopolymers, and then dried under vacuum at 60°C to obtain modified polycaprolactam.
[0056] S3 polyethylene terephthalate graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare a sterile modified solvent;
[0057] 2-Methacryloxyethyltrimethylammonium chloride 120 g / L
[0058] N,N'-Methylenebisacrylamide 2.4 g / L
[0059] The activated polyethylene terephthalate was immersed in a sterile modified solvent at a bath ratio of 1:40; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0060] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 65°C for 2.5 h.
[0061] After the reaction was completed, the sample was washed twice with 70°C ethanol-water solution (volume ratio 1:1), rinsed with deionized water until neutral, and dried at 70°C to obtain polyethylene terephthalate graft.
[0062] S4 Blending Treatment: Modified polycaprolactam and modified polyethylene terephthalate are placed separately into a screw mill. The screw temperature for modified polycaprolactam is 240-260℃; the screw temperature for modified polyethylene terephthalate is 270-290℃. They are mixed and spun using parallel composite spinnerets at a mass ratio of 3:7. The spinning speed is 1200m / min; the draw ratio is 3.5; and the heat setting temperature is 110℃.
[0063] Then, a plain weave fabric is woven using an air-jet loom with a warp and weft density of 320 threads / 10cm × 280 threads / 10cm, a weaving speed of 500r / min, and a fabric width of 150cm to obtain the basic fabric.
[0064] S5 finishing: Add the following ingredients to deionized water to prepare the finishing agent;
[0065]
[0066] The silver-doped nano-titanium sol contains 1.5 wt% silver and 30% waterborne polyurethane solids.
[0067] The process involves two dips and two rolls, with a roll-out rate of ≥75% and a machine speed of 20m / min.
[0068] After the second impregnation, the base fabric is removed, pre-dried with hot air at 80℃ for 3 minutes, then baked at 150℃ for 2 minutes; finally, it is washed with warm water at 50℃ and dried to obtain the mixed fiber.
[0069] Example 2: Preparation method of mixed fibers
[0070] The difference from Example 1 is that in step S4, the mass ratio of modified polycaprolactam and modified polyethylene terephthalate in the blending process is 4:6.
[0071] Example 3: A method for preparing mixed fibers, comprising the following steps:
[0072] S1 fiber pretreatment: Polyethylene terephthalate fiber was soaked in 5 g / L NaOH solution (60℃) for 30 min to remove surface oil and impurities, rinsed with deionized water until neutral, and vacuum dried at 80℃ for 4 h.
[0073] Then, under an oxygen atmosphere, the surface-active groups were increased by plasma treatment at 50W for 5 minutes to obtain activated polyethylene terephthalate and polycaprolactam.
[0074] S2 polyethylene terephthalate graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare a sterile modified solvent;
[0075] 2-Methacryloxyethyltrimethylammonium chloride 120 g / L
[0076] N,N'-Methylenebisacrylamide 2.4 g / L
[0077] The activated polyethylene terephthalate was immersed in a sterile modified solvent at a bath ratio of 1:40; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0078] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 65°C for 2.5 h.
[0079] After the reaction was completed, the sample was washed twice with 70°C ethanol-water solution (volume ratio 1:1), rinsed with deionized water until neutral, and dried at 70°C to obtain polyethylene terephthalate graft.
[0080] S4 blending treatment: Polycaprolactam and modified polyethylene terephthalate are placed separately into a screw mill. The screw temperature for polycaprolactam is 240-260℃; the screw temperature for modified polyethylene terephthalate is 270-290℃; they are mixed and spun using parallel composite spinnerets at a mass ratio of 3:7; the spinning speed is 1200m / min; the draw ratio is 3.5; and the heat setting temperature is 110℃.
[0081] Then, a plain weave fabric is woven using an air-jet loom with a warp and weft density of 320 threads / 10cm × 280 threads / 10cm, a weaving speed of 500r / min, and a fabric width of 150cm to obtain the basic fabric.
[0082] S5 finishing: Add the following ingredients to deionized water to prepare the finishing agent;
[0083]
[0084] The silver-doped nano-titanium sol contains 1.5 wt% silver and 30% waterborne polyurethane solids.
[0085] The process involves two dips and two rolls, with a roll-out rate of ≥75% and a machine speed of 20m / min.
[0086] After the second impregnation, the base fabric is removed, pre-dried with hot air at 80℃ for 3 minutes, then baked at 150℃ for 2 minutes; finally, it is washed with warm water at 50℃ and dried to obtain the mixed fiber.
[0087] Example 4: A method for preparing mixed fibers, comprising the following steps:
[0088] S1 fiber pretreatment: Polycaprolactam fiber was soaked in 5 g / L NaOH solution (60℃) for 30 min to remove surface oil and impurities, rinsed with deionized water until neutral, and vacuum dried at 80℃ for 4 h;
[0089] Then, under an oxygen atmosphere, the surface-active groups were increased by plasma treatment at 50W for 5 minutes to obtain activated polyethylene terephthalate and polycaprolactam.
[0090] S2 polycaprolactam graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare an electrostatic modification solvent;
[0091] 150 g / L of quaternized dimethylaminoethyl methacrylate
[0092] N,N'-Methylenebisacrylamide 4.5 g / L
[0093] Sodium dodecyl sulfate 1 g / L.
[0094] The activated polycaprolactam was immersed in an electrostatically modified solvent with a bath ratio of 1:50; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0095] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 55°C for 3 hours.
[0096] After the reaction was completed, the product was washed three times with deionized water at 80°C to remove ungrafted monomers and homopolymers, and then dried under vacuum at 60°C to obtain modified polycaprolactam.
[0097] S4 blending treatment: Modified polycaprolactam and polyethylene terephthalate are placed separately into a screw mill. The screw temperature for modified polycaprolactam is 240-260℃; the screw temperature for polyethylene terephthalate is 270-290℃. They are mixed and spun using parallel composite spinnerets at a mass ratio of 3:7. The spinning speed is 1200m / min; the draw ratio is 3.5; and the heat setting temperature is 110℃.
[0098] Then, a plain weave fabric is woven using an air-jet loom with a warp and weft density of 320 threads / 10cm × 280 threads / 10cm, a weaving speed of 500r / min, and a fabric width of 150cm to obtain the basic fabric.
[0099] S5 finishing: Add the following ingredients to deionized water to prepare the finishing agent;
[0100]
[0101] The silver-doped nano-titanium sol contains 1.5 wt% silver and 30% waterborne polyurethane solids.
[0102] The process involves two dips and two rolls, with a roll-out rate of ≥75% and a machine speed of 20m / min.
[0103] After the second impregnation, the base fabric is removed, pre-dried with hot air at 80℃ for 3 minutes, then baked at 150℃ for 2 minutes; finally, it is washed with warm water at 50℃ and dried to obtain the mixed fiber.
[0104] Example 5: A method for preparing mixed fibers, comprising the following steps:
[0105] S1 fiber pretreatment: Polyethylene terephthalate fiber and polycaprolactam fiber were soaked in 5 g / L NaOH solution (60℃) for 30 min to remove surface oil and impurities, rinsed with deionized water until neutral, and vacuum dried at 80℃ for 4 h.
[0106] S2 blending treatment: Polycaprolactam and polyethylene terephthalate are placed separately into a screw mill. The screw temperature for polycaprolactam is 240-260℃; the screw temperature for polyethylene terephthalate is 270-290℃. They are mixed and spun using parallel composite spinnerets at a mass ratio of 3:7. The spinning speed is 1200m / min; the draw ratio is 3.5; and the heat setting temperature is 110℃.
[0107] Then, a plain weave fabric is woven using an air-jet loom with a warp and weft density of 320 threads / 10cm × 280 threads / 10cm, a weaving speed of 500r / min, and a fabric width of 150cm to obtain the basic fabric.
[0108] S5 finishing: Add the following ingredients to deionized water to prepare the finishing agent;
[0109]
[0110]
[0111] The silver-doped nano-titanium sol contains 1.5 wt% silver and 30% waterborne polyurethane solids.
[0112] The process involves two dips and two rolls, with a roll-out rate of ≥75% and a machine speed of 20m / min.
[0113] After the second impregnation, the base fabric is removed, pre-dried with hot air at 80℃ for 3 minutes, then baked at 150℃ for 2 minutes; finally, it is washed with warm water at 50℃ and dried to obtain the mixed fiber.
[0114] Example 6: A method for preparing mixed fibers, comprising the following steps:
[0115] S1 fiber pretreatment: Polyethylene terephthalate fiber and polycaprolactam fiber were soaked in 5 g / L NaOH solution (60℃) for 30 min to remove surface oil and impurities, rinsed with deionized water until neutral, and vacuum dried at 80℃ for 4 h.
[0116] Then, under an oxygen atmosphere, the surface-active groups were increased by plasma treatment at 50W for 5 minutes to obtain activated polyethylene terephthalate and polycaprolactam.
[0117] S2 polycaprolactam graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare an electrostatic modification solvent;
[0118] 150 g / L of quaternized dimethylaminoethyl methacrylate
[0119] N,N'-Methylenebisacrylamide 4.5 g / L
[0120] Sodium dodecyl sulfate 1 g / L.
[0121] The activated polycaprolactam was immersed in an electrostatically modified solvent with a bath ratio of 1:50; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0122] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 55°C for 3 hours.
[0123] After the reaction was completed, the product was washed three times with deionized water at 80°C to remove ungrafted monomers and homopolymers, and then dried under vacuum at 60°C to obtain modified polycaprolactam.
[0124] S3 polyethylene terephthalate graft modification: Add the following components to deionized water at the following concentrations and adjust the pH to 6.0 to prepare a sterile modified solvent;
[0125] 2-Methacryloxyethyltrimethylammonium chloride 120 g / L
[0126] N,N'-Methylenebisacrylamide 2.4 g / L
[0127] The activated polyethylene terephthalate was immersed in a sterile modified solvent at a bath ratio of 1:40; nitrogen gas was then introduced to remove oxygen for 10 minutes.
[0128] Then, 1.5 mmol / L ammonium persulfate was added as an initiator, and the reaction was carried out in a constant temperature water bath at 65°C for 2.5 h.
[0129] After the reaction was completed, the sample was washed twice with 70°C ethanol-water solution (volume ratio 1:1), rinsed with deionized water until neutral, and dried at 70°C to obtain polyethylene terephthalate graft.
[0130] S4 Blending Treatment: Modified polycaprolactam and modified polyethylene terephthalate are placed separately into a screw mill. The screw temperature for modified polycaprolactam is 240-260℃; the screw temperature for modified polyethylene terephthalate is 270-290℃. They are mixed and spun using parallel composite spinnerets at a mass ratio of 3:7. The spinning speed is 1200m / min; the draw ratio is 3.5; and the heat setting temperature is 110℃.
[0131] Then, a plain weave fabric is woven using an air-jet loom with a warp and weft density of 320 threads / 10cm × 280 threads / 10cm, a weaving speed of 500r / min, and a fabric width of 150cm. The fabric is then washed in 50℃ warm water and dried to obtain mixed fibers.
[0132] Performance testing
[0133] The performance of the blended fibers prepared in the above embodiments was tested, specifically as follows:
[0134] Antistatic effect: Tested according to the method of GB / T 12703.1-2021 Textiles - Test Methods for Electrostatic Properties - Part 1: Corona Charging Method.
[0135] Antibacterial effect: Tested according to the method in GB / T 20944.2-2007 Evaluation of antibacterial properties of textiles - Part 2: Absorption method.
[0136] Wash resistance test: Following the method described in GB / T 8629-2017 "Test Procedures for Household Washing and Drying of Textiles", the product was washed 50 times in program 5A; then, antistatic and antibacterial effects were tested again. The results are shown in Table 1 below:
[0137] Table 1
[0138]
[0139] The present invention considers Examples 1 and 2 to be the most complete process, with the performance difference being the different ratios of polycaprolactam and polyethylene terephthalate; this demonstrates the synergistic enhancement and wash resistance advantages of graft modification and finishing, and also shows that increasing the proportion of antistatic fibers can specifically optimize electrostatic performance.
[0140] Example 3 lacks polycaprolactam grafting. S2 polycaprolactam antistatic grafting was not performed; only polyester antibacterial grafting and finishing were retained. Before washing, antibacterial properties remained excellent (>98.5%), but antistatic properties deteriorated significantly (2.0 s). After 50 washes, antistatic properties decreased sharply (5.0 s), while antibacterial properties remained acceptable (>89.5%), highlighting the insufficient durability due to the lack of antistatic grafting.
[0141] Example 4 lacked polyester grafting and did not undergo S3 polyester antibacterial grafting; only polycaprolactam antistatic grafting and post-treatment were retained. Before washing, antistatic properties were good (0.5s), but antibacterial properties decreased significantly (<85%); after 50 washes, antibacterial properties further decreased to <70%, demonstrating that antibacterial performance is highly dependent on the chemical bonding of the polyester grafting.
[0142] Example 5 involved no grafting modification and relied solely on post-treatment. Performance was worst before washing (half-life 3.0s, antibacterial rate <80%); performance collapsed after 50 washes (half-life 10.0s, antibacterial rate <50%), confirming that the post-treatment agent had extremely low wash resistance without grafting modification.
[0143] Example 6 involved no post-treatment, completing the dual-fiber grafting modification but skipping the S5 post-treatment. Before washing, the antistatic properties (1.0s) and antibacterial properties (>94%) were good but weaker than in Example 1; after 50 washes, the performance showed almost no degradation (antibacterial rate...).
[0144] >93%, half-life 1.2s), demonstrating the excellent washability of graft-modified products, but lacking the immediate enhancement effect of post-treatment.
[0145] Examples 1, 2, 4 and 6 showed good antistatic properties before washing (half-life ≤ 1.0s) due to polycaprolactam grafting or a high proportion; after washing, the grafted modified cases (such as Examples 1, 2 and 6) showed little change, while the post-finishing dependent cases (such as Examples 3 and 5) deteriorated significantly.
[0146] Examples 1, 2, 3, and 6 exhibited high antibacterial rates (≥95%) before washing due to polyester grafting. After washing, the grafted modified cases (e.g., Examples 1, 2, and 6) maintained >90%, while the finishing-dependent cases (e.g., Examples 4 and 5) decreased to <70%.
[0147] The key role of grafting modification in this invention is explained: polycaprolactam grafting (quaternary ammonium salt monomer) mainly provides long-lasting antistatic properties, while polyester grafting (quaternary ammonium salt monomer) mainly provides long-lasting antibacterial properties, and the chemical bond structure between the two ensures washability.
[0148] The auxiliary value of post-treatment: It provides immediate performance enhancement (especially before washing), but physically adsorbed components (polythiophene, silver nanoparticles) are easily detached during washing.
[0149] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an antistatic and antibacterial blended fiber, characterized in that, Includes the following steps: S1 fiber pretreatment: polyethylene terephthalate fibers and polycaprolactam fibers are washed and then dried; then they are activated. Activated polyethylene terephthalate and polycaprolactam were obtained; S2 polycaprolactam graft modification: Quaternized dimethylaminoethyl methacrylate, N,N'-methylenebisacrylamide and emulsifier are added to deionized water, stirred to dissolve and the pH is adjusted to 6.0 to obtain electrostatic modified solvent; The activated polycaprolactam was immersed in an electrostatically modified solvent and deoxygenated, and then an initiator was added and the mixture was heated in a water bath for reaction. After the reaction is complete, wash the reactants and then dry them; Modified polycaprolactam was obtained; S3 polyethylene terephthalate graft modification: 2-methacryloyloxyethyltrimethylammonium chloride and N,N'-methylenebisacrylamide are added to deionized water; the mixture is stirred to dissolve and the pH is adjusted to 6.0 to obtain a sterile modified solvent; The activated polyethylene terephthalate was immersed in a sterile modified solvent and deoxygenated, and then an initiator was added and the mixture was heated in a water bath for reaction. After the reaction was complete, the reactants were washed and then dried to obtain modified polyethylene terephthalate. S4 blending treatment: Modified polycaprolactam and modified polyethylene terephthalate are placed separately into a screw press and spun together at a mass ratio of 3-4:6-7 to obtain the base fabric; S5 finishing: The base fabric is immersed in the finishing agent and then treated by padding-baking method to obtain antistatic and antibacterial blended fiber.
2. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S2, the quaternized dimethylaminoethyl methacrylate is generated by a nucleophilic substitution reaction between dimethylaminoethyl methacrylate and a haloalkane.
3. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S2, the electrostatically modified solvent contains the following components by concentration: Quaternized dimethylaminoethyl methacrylate ≥150g / L N,N'-methylenebisacrylamide ≥4.5 g / L Emulsifier ≥1g / L.
4. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S2, when the activated polycaprolactam is immersed in the electrostatic modification solvent, the bath ratio is 1:≥50; the amount of initiator added is ≥1.5mmol / L; the temperature of the water bath reaction is ≥55℃, and the time is ≥3h.
5. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S3, the antibacterial modified solvent contains the following components by concentration: 2-Methacryloxyethyltrimethylammonium chloride ≥120g / L N,N'-methylenebisacrylamide ≥2.4 g / L.
6. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S3, when the activated polyethylene terephthalate is immersed in the sterile modified solvent, the bath ratio is 1:≥40; the amount of initiator added is ≥1.5mmol / L; the temperature of the water bath reaction is ≥65℃ and the time is ≥2.5h.
7. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S5, the finishing agent contains the following components based on concentration: The silver-doped nano-titanium sol contains at least 1.5 wt% silver; the aqueous polyurethane has a solid content of ≥30%.
8. The method for preparing antistatic and antibacterial blended fibers according to claim 1, characterized in that, In step S5, the dip-and-bake method involves at least two dips and two rolls, with a roll yield ≥75%; the baking temperature ≥150℃ and the baking time ≥2min.
Citation Information
Cited By
PMMA (polymethyl methacrylate) based on N-ethylene caprolactam modification and application thereof
CN121673481A